Mathematical Representation Abilities in Bruner’s Representation Stages: A Phenomenological Study of High School Students - Puspita Helena; Krisna Satrio Perbowo ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2026)
Mathematical representation ability is important in helping students understand mathematical concepts and solve problems meaningfully. However, studies on mathematical representation abilities through Bruner’s stages of representation remain limited, while students still experience difficulties in connecting various forms of representation. This study aims to describe the characteristics of students' mathematical representation abilities at each stage of Jerome Bruner’s development. The study employed a qualitative method with a phenomenological approach involving 104 tenth-grade high school students in Indonesia selected through purposive sampling. Data were collected through mathematical representation tests, Focus Group Discussions (FGD), and non-systematic observation sheets, then analyzed thematically, with themes derived entirely from students’ responses to address the research questions. The results indicate that students' mathematical representation abilities vary across Bruner’s stages of representation. In the enactive stage, students use object manipulation to understand problems, although not optimally. In the iconic stage, students use visual representations such as tables, figures, and diagrams, but some are still unsystematic and do not fully reflect the problem structure. At the symbolic stage, students are able to construct mathematical models and apply algebraic procedures, although errors in modeling, method application, and calculation are still found. In addition, students’ verbal representation abilities remain limited, as indicated by their difficulty in drawing conclusions that connect results to the problem context. These findings indicate that mastery of the enactive and iconic stages contributes to students’ success in reaching symbolic representation and may serve as a basis for developing more meaningful mathematics learning strategies.